Reconsidering the Existence of Muhkam and Mutasyabbih in Contemporary Qur’anic Studies: Meninjau Kembali Eksistensi Muhkam dan Mutasyabbih dalam Kajian Al-Qur’an Kontemporer - Eljambaki, Gusnanda; Ikhlas, Nur (Institut Agama Islam Negeri Kerinci, 2023)
This paper discusses the importance of the study of muhkam and mutasyabbih verses in contemporary Qur'anic studies. The discussion of muhkam and mutasyabbih lately seems to be pushed aside by contemporary approaches that mainly come from Western scholars. Despite being an inseparable part of the classical scholars' products, the discussion of muhkam and mutasyabbih verses is still very relevant to be discussed in this era. This research is library research with a descriptive-analytical approach. The material object of this research is taken from the books of Ulum al-Qur'an from classical to contemporary. As for analyzing it, the author uses theories from Muslim scholars and scholars about the position of the theory of ulum al-Qur'an related to the research problem. The results of the study in this paper concluded that the concept or theme of muhkam and mutasyabbih is a basic theory in the study of al-Qur'anic science formulated by Eastern scholars in the classical era. This theory is well-established and very fundamental. It is grouped as one of the branches of ulum al-Qur'an. Someone who will understand the Qur'an and explore the meaning of the Qur'an must master this branch of science. However, the established theory was shaken because of the results of Western scholars' studies of the Qur'an. The influence of Western studies on the Qur'an makes the Qur'anic scholars seem to discredit the study of muhkam and mutasyabbih. There is even an assumption that the study of muhkam and mutasyabbih is classic and outdated. Whereas without this study someone will not be able to map and explore the meaning of the Qur'an which is so broad and deep. For a Muslim, the Qur'an is a divine manifestation that cannot be doubted. This view is contrary to Western epistemology which always starts from suspicion. Therefore, the study of muhkam and mutasyabbih is still very significant to be discussed in this contemporary era. It cannot only be considered an intellectual treasure of classical scholars but also as an authoritative rule in understanding the Qur'an.